Adverse pregnancy outcome in rats following exposure to a Salacia reticulata (Celastraceae) root extract - W.D. Ratnasooriya; J.R.A.C. Jayakody; G.A.S. Premakumara (Brazilian Journal of Medical and Biological Research, 2003)
The root extract of Salacia reticulata Wight (family: Celastraceae) is used in Sri Lanka by traditional practitioners as a herbal therapy for glycemic control even during pregnancy. It is recognized that some clinically used antidiabetic drugs have harmful effects on pregnancy but the effects of the S. reticulata root extract on reproductive outcome is unknown and deserves examination. We determined the effects of the S. reticulata root extract on the reproductive outcome of Wistar rats (250-260 g) when administered orally (10 g/kg) during early (days 1-7) and mid- (days 7-14) pregnancy. The root extract significantly (P<0.05) enhanced post-implantation losses (control vs treatment: early pregnancy, 4.7 ± 2.4 vs 49.3 ± 13%; mid-pregnancy, 4.7 ± 2.4 vs 41.7 ± 16.1%). Gestational length was unaltered but the pups born had a low birth weight (P<0.05) (early pregnancy, 6.8 ± 0.1 vs 5.3 ± 0.1 g; mid-pregnancy, 6.8 ± 0.1 vs 5.0 ± 0.1 g) and low birth index (P<0.05) (early pregnancy, 95.2 ± 2.4 vs 50.7 ± 12.9%; mid-pregnancy, 95.2 ± 2.4 vs 58.3 ± 16.1%), fetal survival ratio (P<0.05) (early pregnancy, 95.2 ± 2.4 vs 50.7 ± 12.9; mid-pregnancy, 95.2 ± 2.4 vs 58.3 ± 16.1), and viability index (P<0.05) (early pregnancy, 94.9 ± 2.6 vs 49.5 ± 12.5%; mid-pregnancy, 94.9 ± 2.6 vs 57.1 ± 16.1%). However, the root extract was non-teratogenic. We conclude that the S. reticulata root extract can be hazardous to successful pregnancy in women and should not be used in pregnancy complicated by diabetes.